2018
DOI: 10.1200/jco.2018.36.6_suppl.11
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of 6 months ADT/abiraterone acetate plus prednisone (AAP) and definitive radiotherapy (AbiRT) for men with intermediate to high risk localized prostate cancer.

Abstract: 11 Background: Combined external beam radiotherapy (RT) and androgen deprivation therapy (ADT) improves survival over RT alone for high risk prostate cancer (PC). Long-term ADT use, currently recommended for high risk PC, also increases toxicity. Recent data suggests synergistic efficacy with the addition of abiraterone acetate plus prednisone (AAP) to RT/ADT. Potent androgen blockade may provide biochemical control with short-term ADT course in men with aggressive but localized PC. Methods: This was a two ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Three trials of abiraterone combined with rt were found (Table iv). A single phase i study investigated the safety of combining abiraterone with salvage rt 54 and two phase ii trials evaluated efficacy based on the extent of castration as assessed by testosterone level 52,53 . The two phase ii trials varied in their populations and adt durations.…”
Section: Clinical Trials Combining Abiraterone Acetate With Rtmentioning
confidence: 99%
“…Three trials of abiraterone combined with rt were found (Table iv). A single phase i study investigated the safety of combining abiraterone with salvage rt 54 and two phase ii trials evaluated efficacy based on the extent of castration as assessed by testosterone level 52,53 . The two phase ii trials varied in their populations and adt durations.…”
Section: Clinical Trials Combining Abiraterone Acetate With Rtmentioning
confidence: 99%